Determinants factors of OFDI: comparison between Malaysia & Korea / Muhammad Munir Manggar and Nurul Atiqah Shaari - Manggar, Muhammad Munir; Shaari, Nurul Atiqah (Faculty of Business and Management, 2014)
Outward Foreign Direct Investment (OFDI) are one of the strategy for company expand and growth over the world in order to get profit and grab opportunities that can be found in another country. Malaysia and Korea also the countries that involving and implementing OFDI around the world because of various reasons such as human capital, technology, politic, and so forth. This research seeks to study the determinant factor of Outward Foreign Direct Investment by make a comparison between Malaysia and Korea. This Comparison can be a benchmark for Malaysia to make a strategy and move forward in increasing OFDI in Malaysia. The independent variable used in this research was Gross Domestic Product, Export and Exchange Rate. The data used in this paper is annually data range from 1983- 2012 which is 30 years. By using Multiple Linear Regression Model, we found out that Export play a significant role in push out Malaysia OFDI while Korea significant factor was Gross Domestic Product.